Dietary sources, current intakes, and nutritional role of omega‐3 docosapentaenoic acid. Issue 4 (19th March 2015) - Byelashov, Oleksandr A.; Sinclair, Andrew J.; Kaur, Gunveen
<x xml:space="preserve">Abstract</x> Fish oils and long‐chain omega‐3 fatty acids are well recognized for their critical role in human diets. Docosapentaenoic acid (DPA, 22 : 5n‐3) has always been a part of healthy nutrition, since infants obtain almost as much DPA as DHA from human milk. Fish oil supplements and ingredients, oily fish, and grass‐fed beef can serve as the primary DPA sources for the general population. Although the DPA levels in fish oils are substantially lower than those of EPA and DHA, concentrated DPA products are now becoming commercially available, and DPA‐based drugs are under development. Epidemiological studies show that similar to eicosapentaenoic (EPA, 20 : 5n‐3) and docosahexaenoic (DHA, 22 : 6n‐3) acids, DPA is linked to various improvements in human health, perhaps owing to its structural similarity to the other two molecules. Studies in mammals, platelets, and cell cultures have demonstrated that DPA reduces platelet aggregation, and improves lipid metabolism, endothelial cell migration, and resolution of chronic inflammation. Further, other in vivo and in vitro studies have shown that DPA can improve neural health. A human supplementation trial with 99.8% pure DPA suggested that it serves as a storage depot for EPA and DHA in the human body. Future randomized controlled human trials with purified DPA will help clarify its effects on human health. They may confirm the available evidence pointing to its nutritional and biological functions, unique or overlapping with those of EPA and DHA.